2023
DOI: 10.3390/ijms24021261
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of the GRF Gene Family in Melastoma dodecandrum

Abstract: Growth-regulating factor (GRF) is a kind of transcription factor unique to plants, playing an important role in the flowering regulation, growth, and development of plants. Melastoma dodecandrum is an important member of Melastomataceae, with ornamental, medicinal, and edible benefits. The identification of the GRF gene family in M. dodecandrum can help to improve their character of flavor and continuous flowering. The members of the GRF gene family were identified from the M. dodecandrum genome, and their bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…GA3 treatment enhanced the expression of OsGRF in rice (Choi et al, 2004). In addition, studies have shown that ABA, MeJA, and GA3 treatments cause signi cant differences in the expression levels of CsGRF genes in most Melastoma dodecandrum (Huang et al, 2023). We found a regulatory element for avonoid biosynthesis genes in AmGRF3, and overexpression of the AmGRF3 gene leads to avonoid accumulation.…”
Section: Discussionmentioning
confidence: 62%
“…GA3 treatment enhanced the expression of OsGRF in rice (Choi et al, 2004). In addition, studies have shown that ABA, MeJA, and GA3 treatments cause signi cant differences in the expression levels of CsGRF genes in most Melastoma dodecandrum (Huang et al, 2023). We found a regulatory element for avonoid biosynthesis genes in AmGRF3, and overexpression of the AmGRF3 gene leads to avonoid accumulation.…”
Section: Discussionmentioning
confidence: 62%
“…In contrast, LcWRKY47 had no introns. The identified LcWRKY genes also differed in terms of size, ranging from 879 bp ( LcWRKY29 in group III) to 8348 bp ( LcWRKY10 in group I) [ 45 ] ( Supplementary Files S1 and S5 ). The LcWRKY gene sizes in group I ranged from 1578 bp ( LcWRKY43 ) to 8348 bp ( LcWRKY10 ).…”
Section: Resultsmentioning
confidence: 99%
“…The YABBY protein sequences of A. thaliana , P. granatum , J. curcas , and E. grandis were used as a reference, the local Blast search was performed by TBtools [ 31 ], and the candidate genes of YABBY gene family in M. dodecandrum were screened at an E-value of <1 × 10 −5 . Then, the Pfam database ( , accessed on 16 November 2022) and NCBI Batch CD-search ( , accessed on 16 November 2022) were used to verify the conserved domain of YABBY proteins [ 32 ]. The length of amino acid, the molecular weight, the instability index, the aliphatic index, the grand average of hydropathicity, and the isoelectric point of YABBY proteins in the M. dodecandrum were analyzed by ExPasy ( (accessed on 17 November 2022) [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…A Taq Pro Universal SYBR qPCR Master Mix kit (Vazyme, Nanjing, China) was used for the RT-qPCR analysis. The MdActin gene was used as an internal reference [ 32 ], and the biological repetition and technical repetition were performed three times. The expression level was calculated by the 2 −∆Ct method [ 1 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation